2012
DOI: 10.3109/17453674.2012.736169
|View full text |Cite
|
Sign up to set email alerts
|

Minimally invasive surgery did not improve outcome compared to conventional surgery following unicompartmental knee arthroplasty using local infiltration analgesia

Abstract: Background and purpose There has recently been interest in the advantages of minimally invasive surgery (MIS) over conventional surgery, and on local infiltration analgesia (LIA) during knee arthroplasty. In this randomized controlled trial, we investigated whether MIS would result in earlier home-readiness and reduced postoperative pain compared to conventional unicompartmental knee arthroplasty (UKA) where both groups received LIA.Patients and methods 40 patients scheduled for UKA were randomized to a MIS gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0
1

Year Published

2013
2013
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 17 publications
1
6
0
1
Order By: Relevance
“…The assessments focused on functional outcome measures during the recovery from knee replacement in the first six months. We did not attempt to compare pain medication levels in the two groups which has been the subject of previous studies [ 18 , 19 ] investigating the effects of surgical approach.…”
Section: Discussionmentioning
confidence: 99%
“…The assessments focused on functional outcome measures during the recovery from knee replacement in the first six months. We did not attempt to compare pain medication levels in the two groups which has been the subject of previous studies [ 18 , 19 ] investigating the effects of surgical approach.…”
Section: Discussionmentioning
confidence: 99%
“…A total of 1678 relevant studies were obtained in the initial search of the PubMed (n = 190), EMBASE (n = 477), Cochrane Library (n = 531), and Web of Science (n = 460) databases, as well as from manual retrieval (n = 20). After excluding duplicate literature and applying the inclusion criteria and exclusion criteria, 51 RCTs 15, were finally included in this study, of which 42 15,[29][30][31][32][33][34][35][36][37][39][40][41][42][43][44][45][46][47][49][50][51][52][53][54][55][56][57][58][59][62][63][65][66][67][70][71][72][73][74][75][76] were clearly approved by ethics committees, while the approval of nine was not reported. Two three-arm tests were included in the analysis, while the remainder were all two-arm tests.…”
Section: Literature Screening Process and Resultsmentioning
confidence: 99%
“…In this study, the mean surgical incision in both groups was over 12 cm long, similar to conventional surgery. However, it has been reported that even with minimally invasive surgery of UKA (an 8 to 10 cm-long medial parapatellar skin incision), pain scores and functional outcomes were not improve by using LIA alone [37]. Considering the surgical area of nerve innervation in medial UKA, continuous ACB may be uniquely suited to provide postoperative analgesia.…”
Section: Discussionmentioning
confidence: 99%